Die eerste “Ebed-Jahwelied” in Jesaja 42:1-9: eksegetiese, teologiese en homiletiese oorwegings - Snyman, SD (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
The first “Ebed-Yahweh song in Isaiah 42:1-9: exegetical, theological and homiletical considerations The aim of this article is to provide an exegesis of Isaiah 42:1-9 paying attention to the literary and historical aspects of the text. On the basis of this investigation some theological conclusions are drawn. Taking the theological dimension of the text into consideration some homiletical guidelines are given in order to prepare a sermon from this text.